Porang Tubers - Nisa Rahmaniyah Utami; Muhammad Almiraji (Media Pendidikan Gizi dan Kuliner, 2021)
Porang tubers are plants that have many benefits and are rich sources of vitamins and protein as well as many uses for both food and as flour/main ingredient in the manufacture of foods such as cakes and noodles. However, it is unfortunate that there is still a lack of utilization of porang tubers flour as a food source. Therefore, the author made a kastangel cake with the addition of porang tuber flour to further develop the use of porang bulbs flour as a cake base and to find out the interest of the surrounding community towards the preference for products made with porang tuber ingredients. This study uses a questionnaire method with a preference test from the panelists, then the authors look for information on a good formulation to be applied to the kastangel cake before being tested on the panelists. Which later the author will record the answers of respondents from the results of the questionnaire. The author finds out the results of the study by looking for the mean, median, mode, and standard deviation data. The results are obtained by taking the average value of 4 (four) aspects, namely color, aroma, texture, taste in kastangel cake. (30% porang tuber flour 70% wheat flour) with an overall value of 38.68 consumer panelists with an average of 3.22 and for expert panelists to like kastangel cakes with formulations (30% porang tuber flour and 70% wheat flour) with the total score is 41.2 with an average of 3.22. The results of this study indicate that the use of porang tuber flour in making kastangel cake can be said to be successful with the results of the preference test which are dominated by liking.